Mental health and behavioural difficulties in adopted children: A systematic review of post-adoption risk and protective factors. (December 2021) - Duncan, Morvwen; Woolgar, Matt; Ransley, Rachel; Fearon, Pasco
Previous research suggests that adopted children are at a greater risk of experiencing psychological and behavioural difficulties or accessing mental health services than non-adopted peers and that post-adoption variables are significant risk and protective factors producing this situation. This review seeks to summarise the post-adoption variables associated with adopted children's mental health or behavioural difficulties to inform future research and shape interventions. A search for publications that assess associated risk and protective factors using Web of Science, Psychinfo, Medline and Sociological Abstracts identified 52 studies that met rigorous methodological criteria. Children's and adolescents' mental health and behavioural outcomes were associated with parent, parent–child and wider family factors and by contextual variables. The findings highlight the importance of focusing on the multitude of systemic factors surrounding a child following adoption. Clinical implications and direction for future research are discussed.